Lean six sigma approach to increase process cycle efficiency in palm oil processing at PT. X - Puspita, Riana; Polewangi, Yudi Daeng; Fazri, Muhammad; Refiza; Siregar, Zufri Hasrudy (Jurnal VORTEKS, 2024)
The Indonesian palm oil industry, a global leader in production, faces increasing challenges in maintaining efficiency and quality. This study aims to apply the Lean Six Sigma methodology to enhance production processes by integrating Lean Manufacturing principles with the systematic, data-driven approach of Six Sigma. Using the Define-Measure-Analyze-Improve-Control (DMAIC) framework, the research identifies and mitigates inefficiencies in key stations of a palm oil mill. Novelty lies in the application of Lean Six Sigma to the palm oil industry, demonstrating significant improvements: a 16% increase in process cycle efficiency, a reduction of 70.5 kg in daily fresh fruit bunch (FFB) losses, and a decrease in associated costs by IDR 176,750 per day. The findings underscore the potential for continuous improvement in the industry through the systematic application of Lean Six Sigma.